Substitution elasticities in a CES production framework: An empirical analysis on the basis of non-linear least squares estimations - Simon Koesler; Michael Schymura (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Effectiveness, cost-efficiency and distribution issues are crucial for any form of future regulation. This results in the need for reliable instruments to assess regulations ex ante. Elasticities are key parameters for such instruments. We consistently estimate substitution elasticities for a three level nested CES KLEM production structure on the basis of non-linear least squares estimation procedures. Thereby we take advantage of the new World-Input-Output Database. This allows us for the first time to use one consistent dataset for the estimation process and gives us the opportunity to derive elasticities from the same data which researchers can use to calibrate their simulations. Our results show that compared to standard linear estimations using Kmenta approximations, non-linear estimation techniques perform significantly better. Moreover, during the time period we consider, no significant change in input substitutability takes place over time. Furthermore, we demonstrate that the common practice of using Cobb-Douglas or Leontief production functions in economic models must be rejected for the majority of sectors. In response to this result, we provide a comprehensive set of consistently estimated substitution elasticities covering 35 sectors.
Keywords: 330; Substitution elasticity; CES production function; Policy evaluation